PR10/Bet v1‐like Proteins as Novel Contributors to Plant Biochemical Diversity. (7th September 2020) - Morris, Jeremy S.; Caldo, Kristian Mark P.; Liang, Siyu; Facchini, Peter J.
Abstract: Pathogenesis‐related (PR) proteins constitute a broad class of plant proteins with analogues found throughout nature from bacteria to higher eukaryotes. PR proteins were first noted in plants as part of the hypersensitive response, but have since been assigned an array of biological roles. The PR10/Bet v1‐like proteins are a subset of PR proteins characterized by an ability to bind a wide range of lipophilic ligands, uniquely positioning them as contributors to specialized biosynthetic pathways. PR10/Bet v1‐like proteins participate in the production of plant alkaloids and phenolics including flavonoids, both as general binding proteins and in special cases as catalysts. Owing initially to the perceived allergenic properties of PR10/Bet v1‐like proteins, many were studied at the structural level to elucidate the basis for ligand binding. These studies provided a foundation for more recent efforts to understand higher‐level structural order and how PR10/Bet v1‐like proteins catalyse key reactions in plant pathways. Synthetic biology aimed at reconstituting plant‐specialized metabolism in microorganisms uses knowledge of these proteins to fine‐tune performance in new systems. Abstract : From allergens to enzymes : The PR10/Bet v1‐like protein family includes notorious plant allergens and members that were initially described as antimicrobial defense proteins. Structural studies reveal a large hydrophobic central cavity that binds ligands including phytohormones, flavonoids, and alkaloids. Recent studies implicate PR10/Bet v1‐like proteins in plant biochemistry and reveal them as key tools for synthetic biology applications.